„Gemeinsame Ordnungen“ oder „Grenzen“ - Historiker und der Begriff des Rheinlandes vor dem Ersten Weltkrieg. Justus Hashagen (1877–1961) im Kontex - Mölich, Georg (Les pays de l'entre-deux. Übergangsräume - Grenzregionen - Konfliktzonen. Mit Beiträgen der Jahrestagung 2019 in Saarbrücken, 2021)
Keywords: Rheinland

Dimensions transnationales de la culture politique rhénane, 1815–1848 - Brophy, James M. (Revue d'histoire du XIXe siècle, 2013)
Abstract: „This essay examines the various strands of transnational influences in the Rhineland during the first half of the nineteenth century. The socioeconomic and political life of western Europe irrevocably penetrated the porous borders of the Rhineland. Ranging over the spheres of law, economy, language, religion, print culture, and political practices, the essay deploys the concept of “histoire croisée” to expose the broader transnational communicative spaces that illuminate the political hybridities of Rhenish social and political history. By exposing the breadth of transnational dimensions to Rhenish politics and civil society, this essay posits intercultural exchange as critical for discussions of German citizenship ideals, which include the impulse of democratization.“
Keywords: Politische Kultur; Rheinland

Hoheitsrechte und Besitzungen Karls V. im Rheinland. Von der Mosel bis zur Nordsee. Eine Beschreibung der östlichen Grenze der Erbniederlande - Vilar Sánchez, Juan Antonio (Karl V. 1500–1558. Neue Perspektiven seiner Herrschaft in Europa und Übersee, 2002)
Keywords: Herrschaft; Karl V. (Heiliges Römisches Reich; Kaiser) (1500–1558); Rheinland